2003
DOI: 10.1016/s0002-9440(10)63925-9
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase Type II Plays a Protective Role in Hepatic Injury

Abstract: The up-regulation of "tissue" transglutaminase (TG2) gene has been shown to occur in various pathologies and can lead to severe liver injury; however, its role in the onset of liver damage has not yet been clarified. To address this issue, we have used two experimental settings: carbon tetrachloride (CCl(4))-induced liver injury in wild-type and TG2 knockout mice; and liver biopsies obtained from a large cohort of hepatitis C virus (HCV)-infected patients. Mice lacking TG2 failed to clear the hepatic necrotic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
55
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 40 publications
5
55
0
1
Order By: Relevance
“…AA, arachidonic acid; iNOS, inducible isoform of nitric oxide synthase; iPs, isoprostanes; PGH 2 , prostaglandin H 2 ; PL, phospholipid; PPAR␥, peroxisome proliferator-activated receptor-␥; TGF-␤, transforming growth factor-␤; TLR4, Toll-like receptor 4. injury plays a protective or pathological role. Consistent with a protective role for TG2 in liver damage, treatment of C57BL/6 TG2-deficient mice with the hepatotoxin carbon tetrachloride resulted in an increased incidence of death postinjury, relative to control C57BL/6 mice, an effect associated with an increased inflammatory response and increased ECM accumulation (204). In contrast, consistent with a proapoptotic role for TG2 is the finding that compared with their wild-type mixed-strain (SVJ129-C57BL/6) littermates, apoptosis of hepatocytes from TG2 Ϫ/Ϫ mice was markedly reduced following treatment of isolated hepatocytes with ethanol or treatment of animals with a low dose (0.1 g/g body wt) of the anti-Fas antibody Jo2, which is a known, potent inducer of endothelial cell and hepatocyte apoptosis that contributes to alcohol-induced liver damage (281).…”
Section: Hepatic and Renal Injurymentioning
confidence: 66%
See 2 more Smart Citations
“…AA, arachidonic acid; iNOS, inducible isoform of nitric oxide synthase; iPs, isoprostanes; PGH 2 , prostaglandin H 2 ; PL, phospholipid; PPAR␥, peroxisome proliferator-activated receptor-␥; TGF-␤, transforming growth factor-␤; TLR4, Toll-like receptor 4. injury plays a protective or pathological role. Consistent with a protective role for TG2 in liver damage, treatment of C57BL/6 TG2-deficient mice with the hepatotoxin carbon tetrachloride resulted in an increased incidence of death postinjury, relative to control C57BL/6 mice, an effect associated with an increased inflammatory response and increased ECM accumulation (204). In contrast, consistent with a proapoptotic role for TG2 is the finding that compared with their wild-type mixed-strain (SVJ129-C57BL/6) littermates, apoptosis of hepatocytes from TG2 Ϫ/Ϫ mice was markedly reduced following treatment of isolated hepatocytes with ethanol or treatment of animals with a low dose (0.1 g/g body wt) of the anti-Fas antibody Jo2, which is a known, potent inducer of endothelial cell and hepatocyte apoptosis that contributes to alcohol-induced liver damage (281).…”
Section: Hepatic and Renal Injurymentioning
confidence: 66%
“…TG2 enhances NFB activation and, thus, inflammation in microglial cells, by cross-linking IB␣, which also results in NFB dissociation and nuclear translocation (157). Increased TG2 expression, resulting from increased binding of NFB to the Tgm2 promoter, enhances extracellular TG2 cross-linking activity, a response observed in experimentally induced hepatic fibrogenesis in rats (189) and in patients with hepatic disease, who have increased ECM TG2 levels (204,222). TG2 expression is also enhanced in cartilage tissue by interleukin (IL)-1 (129) and in liver cells by IL-6 (274).…”
Section: Expression Of Tg2 and Inflammatory Mediatorsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 The TG2-null liver treated with CCl 4 fails to clear the necrotic tissue and exhibits a progressive accumulation of ECM with an elevated number of both activated hepatic stellate cells and inflammatory cells, suggesting a protective role for TG2 in liver injury. 35 Thus, both FXIII and TG2 are apparently involved in adult tissue injury and remodeling, 25 and the precise contribution of each molecule to these processes needs to be defined.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of TG2 could be an advantage during endotoxic shock because this deficiency appears to be associated with an activation of NF-B that is transient, thus allowing the restoration of immunological equilibrium. In this context, studies from the TG2 Ϫ/Ϫ knock-out mice revealed that TG2 offers a protection against liver injuries caused by CCl 4 (36,37). Although many reports have shown an association between the levels of TG2 during inflammatory diseases, its regulation and its role in inflammatory process remain poorly understood.…”
Section: Resultsmentioning
confidence: 99%